SINKRONISASI FISKAL DALAM KERANGKA HUBUNGAN KEUANGAN PUSAT-DAERAH DI KABUPATEN PASURUAN DI KABUPATEN PASURUAN - Nadira Surya Shakina; Risma Ayu Pramesti; Indra Devian Lumban Gaol (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2026)
This study analyzes fiscal synchronization within the HKPD framework under Law Number 1 of 2022, with Pasuruan Regency as the empirical case. The research addresses the persistent structural fiscal dependency of Indonesian regional governments despite over two decades of decentralization. Prior studies have predominantly focused on provincial-level fiscal decentralization or technical compliance rather than structural outcomes. Using a qualitative-descriptive policy analysis approach with secondary data from 2019 to 2023, this study evaluates the effectiveness of fiscal synchronization mechanisms, analyzes the empirical impact of HKPD implementation on the APBD revenue structure, and identifies multilayered structural barriers impeding sustainable regional fiscal autonomy. Findings reveal that the fiscal decentralization ratio remains critically low at an average of 20.92%, although regional tax revenue grew gradually from Rp360 billion (2020) toward a Rp471 billion target (2023). The study concludes that without structural reforms in regional tax administration, flexible transfer mechanisms, and genuine capacity-building investment, the HKPD Law risks producing only symbolic compliance rather than substantive fiscal autonomy.